Depressive Symptoms Pada Ibu Hamil dan Bayi Berat Lahir Rendah - Hapisah Djaswadi Dasuki, Yayi Suryo (Fakultas Kedokteran Universitas Gadjah Mada, 2010)
Background: Low birth weight (LBW) poses the biggest contribution toward neonatal mortality and has long- term health consequences for a child. A psychological condition with depressive disorders in pregnant women affects indirectly the risk of LBW. Previous studies show that there have been different arguments about the effect of depressive symptoms toward birth weight.Objective: To investigate the relationship between pregnant women’s depressive symptoms and low birth weight.Method: This was an observational study with an unmatched case control study design. The case was women presenting LBW, including preterm, intra uterine growth restriction (IUGR) and the control was women presenting normal birth weight (> 2.500 grams) with comparison of 1:2. Data were analyzed with univariable analysis, bivariable analysis using chi-square test and multivariable analysis using logistic regression.Results: Proportion of pregnant women’s depressive symptom was 2.8 greater in women presenting LBW than those presenting normal birth weights (>2.500 grams). Pregnant women experiencing depressive symptoms were significantly related to low birth weight (OR=2.8; CI 95%=1.1-7.2). Meanwhile, proportion of history of ANC < 4 times, history of LBW, poor family economic status and disease during pregnancy was greater in women presenting LBW than those presenting normal birth weights (> 2.500 grams).Conclusion: The proportion of pregnant women’s depressive symptoms was likely to be greater in women delivering babies with LBW than in women delivering babies with normal weight (> 2.500 grams). Pregnant women experiencing depressive symptoms were significantly related to low birth weight. Meanwhile, history of ANC < 4 times, history of LBW, poor family economic status and disease during pregnancy were significantly related to low birth weight.Keywords: depressive symptoms, pregnant women, LBW